The Exploration of the Factors Involved in the Maintenance for CSR Programs within an Organisation - Rankin, Frazer (2007)
Abstract Background: Organisations are now participating more strongly than ever in CSR related activities and as a result current research is strongly orientated towards why organisations are participating in CSR. Purpose: This dissertation explores the motivations, and how these change over time, behind the CSR initiatives conducted within MNCs. This is achieved through utilising the frameworks presented by Garriga and Mele (2004); Instrumental, Ethical and Political motivations, but as opposed to using them as independent factors, interpreting them as homogenous. Results: The results of the research have highlighted the difference between initiatives run by individuals and those run by the organisations. With initiatives that are encouraged through the passions of individuals, and pushed through the organisation, the motivations behind these initiatives are very much Ethically orientated, with Political and Instrumental factors being secondary, until they reach the level where they need the organisations support for the development of the initiative. At this point, for the initiative to develop into an organisational initiative, this will only become possible if there are strong Instrumental opportunities which the organisation can utilise, for example competitive advantage, employee retention or product differentiation.